2022
DOI: 10.1039/d2en00393g
|View full text |Cite
|
Sign up to set email alerts
|

Integrating hollow spherical covalent organic frameworks on NH2–MIL-101(Fe) as high performance heterogeneous photocatalysts

Abstract: A novel metal-organic frameworks@porous organic polymers (MOF@POPs) heter junction, i.e., NH2-MIL-101(Fe)@SNW-1 (MS-x), was synthesized based on the post-synthetic covalent modification. In the present work, aldehyde-modified MOFs (NH2-MIL-101(Fe)) were covalently bonded...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Furthermore, the LUMO potential of UiO-66-NH 2 is more negative than that of O 2 /˙O 2− (−0.33 eV per NHE), which is beneficial for the reduction of O 2 to ˙O 2− and reduced H + into H 2 . 43 Meanwhile, the VB of CeO 2 (2.47 eV per NHE) had more positive potential compared to OH-/˙OH (2.4 eV per NHE). 44 It can oxidize the hydroxyl ion to the hydroxyl radical, which can further react with TC and DCP molecules.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, the LUMO potential of UiO-66-NH 2 is more negative than that of O 2 /˙O 2− (−0.33 eV per NHE), which is beneficial for the reduction of O 2 to ˙O 2− and reduced H + into H 2 . 43 Meanwhile, the VB of CeO 2 (2.47 eV per NHE) had more positive potential compared to OH-/˙OH (2.4 eV per NHE). 44 It can oxidize the hydroxyl ion to the hydroxyl radical, which can further react with TC and DCP molecules.…”
Section: Resultsmentioning
confidence: 94%
“…Notably, compared with those of bulk COFs, these hollow COFs have demonstrated enhanced photocatalytic activities in photocatalytic hydrogen evolution, 22,39,72,94,95 CO 2 conversion, 38,96−98 oxidation, 37 and degradation of environmental contaminants. 19,46,85,95,99 In a pioneering work, Zhang et al reported the synthesis of two hollow nanoporous covalent triazine frameworks (CTFs) with varying chemical compositions through a templateassisted method. 19 Because of the highly ordered hollow interconnected pores, the resulting material exhibited a much better photocatalytic activity in the reduction of 4-nitrophenol than that of a bulk COF.…”
Section: Applications Of Hollow Cofsmentioning
confidence: 99%
“…In another work, Cheng et al explored a MOF@COF composite, termed NH 2 −MIL101(Fe)@SNW-1. 95 Because of the coexistence of Lewis acid sites from the Fe clusters in NH 2 −MIL-101(Fe) and Brønsted base sites from the aminal groups in SNW-1, the resulting MOF/COF composite exhibited high activity in the photodegradation of various pollutants and photocatalytic hydrogen evolution. Recently, Do et al presented the synthesis of a hollow nanospherical TpPa-1 through a hard template method.…”
Section: Applications Of Hollow Cofsmentioning
confidence: 99%
See 2 more Smart Citations